Coexistence, Cooperation and Common Security
XVI, 349 p.
Keywords: To remove the threat of nuclear annihilation changes in attitudes are required, such as the acceptance of the concept of common security to take the place of reliance on nuclear deterrence to keep the peace. This book gives an insight into thinking about ways to deal with the crisis.